Effect of Mechanical Dispersion on Physical Properties of Nanoclay Added Polyvinyl Alcohol (PVA) Nanofibrous Mats - Reyhan Keskin; Muhammed Zahid Koc (Progress in Chemical Science Research Vol. 9, 2023)
In this study, polyvinyl alcohol (PVA) polymer and Cloisite 15A, a modified Montmorillonite nanoclay, were used to produce nanofibrous mats via electrospinning technique. Nanofibers provide great opportunities for creating products with new properties via various physical and chemical modifications during or following the production process. Nanofibers bring promising solutions for fundamental problems in our life in various fields such as energy, environmental, and medical treatments. Increased polymer concentration led to bead-free nanofibrous PVA mats. EDX analysis approved nanoclay is present in samples produced from nanoclay added PVA solutions. Mechanical stirring for nanoclay dispersion enabled smooth nanofibrous structures only in low (1/13) nanoclay weight/ polymer weight ratios and showed very little tensile increase from 1 wt % clay loading to 2 wt % addition. The effect of nanoclay addition with magnetic stirring on mechanical properties of nanofibrous mats was evaluated by tensile testing mat samples. Increased nanoclay content in PVA nanofibrous mats did not directly increase tensile strength; this may be because of the negative effects of poor nanoclay distribution on tensile results. Morphological analysis demonstrated that nanofibrous structures were distinct from smooth fibre structures because, as the ratio of nanoclay weight to polymer weight increased, smooth nanofibers became non-uniform fibrous structures.